In the ear of the beholder: how age shapes emotion processing in nonverbal vocalizations - Lima, C. F.; Alves, T.; Scott, S. K.; Castro, S. L. (Emotion, 2014)
It is well established that emotion recognition of facial expressions declines with age, but evidence for age-related differences in vocal emotions is more limited. This is especially true for nonverbal vocalizations such as laughter, sobs, or sighs. In this study, 43 younger adults (M = 22 years) and 43 older ones (M = 61.4 years) provided multiple emotion ratings of nonverbal emotional vocalizations. Contrasting with previous research, which often includes only one positive emotion (happiness) versus several negative ones, we examined 4 positive and 4 negative emotions: achievement/triumph, amusement, pleasure, relief, anger, disgust, fear, and sadness. We controlled for hearing loss and assessed general cognitive decline, cognitive control, verbal intelligence, working memory, current affect, emotion regulation, and personality. Older adults were less sensitive than younger ones to the intended vocal emotions, as indicated by decrements in ratings on the intended emotion scales and accuracy. These effects were similar for positive and negative emotions, and they were independent of age-related differences in cognitive, affective, and personality measures. Regression analyses revealed that younger and older participants' responses could be predicted from the acoustic properties of the temporal, intensity, fundamental frequency, and spectral profile of the vocalizations. The two groups were similarly efficient in using the acoustic cues, but there were differences in the patterns of emotion-specific predictors. This study suggests that ageing produces specific changes on the processing of nonverbal vocalizations. That decrements were not attenuated for positive emotions indicates that they cannot be explained by a positivity effect in older adults.